Podia and Pens: Dismantling the Two-Track System for Legal Research and Writing Faculty - Tiscione, Kristen K.; Vorenberg, Amy (Columbia Journal of Gender and Law, 2015)
At the 2015 AALS Annual Meeting, a panel was convened under this title to discuss whether separate tracks and lower status for legal research and writing (“LRW”) faculty make sense given the current demand for legal educators to better train students for practice. The participants included law professors, an associate dean, and a federal judge.2 Each panelist was asked to respond to questions about the “two-track” system—a shorthand phrase for the two tracks of employment at many law schools whereby full-time LRW faculty are treated differently than tenured and tenure-track faculty. The panelists represented differing views on the topic. This Article grows out of the conversation, information, and ideas that emerged.